2011
DOI: 10.1161/strokeaha.110.608190
|View full text |Cite
|
Sign up to set email alerts
|

Dose Effect of Intraventricular Fibrinolysis in Ventricular Hemorrhage

Abstract: Background and Purpose-The aim of the current study was to investigate the dose-dependent efficacy of intraventricular fibrinolysis (IVF) in patients with severe intraventricular hemorrhage (IVH). Methods-Patients with intracerebral hemorrhage, severe IVH, and obstructive hydrocephalus with the need for external ventricular drainage were treated with IVF through external ventricular drainage. The time course of IVH resolution and the safety profile were compared between patients treated with high-dose IVF (4 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 6 publications
2
17
0
6
Order By: Relevance
“…Studies with rtPA have used various dose regimens ranging from 1 to 4 mg every 8 to 12 hours. 184,[215][216][217][218] The largest trial of intraventricular fibrinolysis to date is the CLEAR-IVH trial (Clot Lysis: Evaluating Accelerated Resolution of IVH). 184,217,218 CLEAR-IVH included 100 patients (22 placebo, 78 rtPA) with IVH attributable to spontaneous ICH <30 mm 3 .…”
Section: Strokementioning
confidence: 99%
“…Studies with rtPA have used various dose regimens ranging from 1 to 4 mg every 8 to 12 hours. 184,[215][216][217][218] The largest trial of intraventricular fibrinolysis to date is the CLEAR-IVH trial (Clot Lysis: Evaluating Accelerated Resolution of IVH). 184,217,218 CLEAR-IVH included 100 patients (22 placebo, 78 rtPA) with IVH attributable to spontaneous ICH <30 mm 3 .…”
Section: Strokementioning
confidence: 99%
“…6 Although not established for SAH, reports on more rapid IVH wash out at higher rt-PA doses were our main impetus to administer higher rt-PA doses during a shorter period of time (4× 5 mg rt-PA >48 hours) because of the necessity of prolonged sedation for concomitant kinetic therapy. 20 However, despite heterogeneous data on the effectiveness and safety in this respect, other studies also suggested lower rt-PA doses until complete blood removal in CT. 17 Nevertheless, the present study is the first randomized trial investigating the effect of intraventricular rt-PA administration to allow the inclusion of patients undergoing either surgical or endovascular repair of ruptured intracranial aneurysm after severe SAH. Despite the higher proportion of conservatively managed subgaleal hematomas in the experimental group, this less invasive and more practical application resulted in safe and highly effective clot reduction, also without altering permanent occlusion of aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, faster and more effective drainage of IVH after lysis may be crucial to attenuate inflammatory damage. 23 Of course, in the absence of experimental or histopathologic data, those interpretations remain speculative. Prospective data are necessary to possibly confirm our data and to address further questions such as influence of ventricular rtPA on periventricular matter.…”
Section: Discussionmentioning
confidence: 99%